THE COMPOSITION AND MEDICINAL PROPERTIES OF ARUGULA (ERUCA SATIVA) (Journal of Universal Science Research, 2025)
Arugula (Eruca sativa), a member of the Brassicaceae family, is a leafy green vegetable widely recognized for its nutritional and medicinal value. This article explores the chemical composition and therapeutic properties of arugula. The plant is rich in essential vitamins such as A, C, and K, as well as minerals including calcium, iron, and potassium. Additionally, it contains bioactive compounds like glucosinolates and antioxidants, which contribute to its health-promoting effects.